Pengaruh penerapan model peta konsep dan penalaran terhadap kemampuan menulis esai mahasiswa - Budiyono, Herman; Aryanti, Puji Tri (citeus, 2016)
This study aims to explain the effect of applying the model to map concepts and reasoning ability of students to write essays High School Teacher Training and Education (STKIP) YPM Bangko, Jambi. The design study is a quasi-experiment, the independent variable (model a concept map), the moderator variable (reasoning), and the dependent variable (the ability to write an essay). 2x2 factorial design used. One treatment with two levels (X1 and X2) and moderator variables that have two tiers (Y1 and Y2). Subjects were two groups: the experimental class and control class. The results showed that there is the effect of applying the model to map concepts and reasoning ability of students to write essays. The application of the model map concept significantly affect the ability to write an essay, the level of a = 0.05, t count> t table (2.946> 2.011).